Vibrio cholerae fur mutations associated with loss of repressor activity: implications for the structural-functional relationships of fur. - Lam, M S (1994)
We used the Vibrio cholerae Fur protein as a model of iron-sensitive repressor proteins in gram-negative bacteria. Utilizing manganese mutagenesis, we isolated twelve independent mutations in V. cholerae fur that resulted in partial or complete loss of Fur repressor function. The mutant fur genes were recovered by PCR and sequenced; 11 of the 12 contained point mutations (two of which were identical), and one contained a 7-bp insertion that resulted in premature truncation of Fur. All of the mutants, except that containing the prematurely truncated Fur, produced protein by Western blot (immunoblot) analysis, although several had substantially smaller amounts of Fur and two made an immunoreactive protein that migrated more rapidly on sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Nine of the 11 point mutations altered amino acids that are identical in all of the fur genes sequenced so far, suggesting that these amino acids may play important structural or functional roles in Fur activity. Eight of the point mutations occurred in the amino-terminal half of Fur, which is thought to mediate DNA binding; most of these mutations occurred in conserved amino acids that have been previously suggested to play a role in the interaction between adjacent alpha-helices of the protein. Three of the point mutations occurred in the carboxy-terminal half of Fur, which is thought to bind iron. One mutation at histidine-90 was associated with complete loss of Fur function; this amino acid is within a motif previously suggested as being involved in iron binding by Fur. The fur allele mutant at histidine-90 interfered with iron regulation by wild-type fur in the same cell when the mutant allele was present at higher copy number; wild-type fur was dominant over all other fur mutant alleles studied. These results are analyzed with respect to previous models of the structure and function of Fur as an iron-sensitive repressor.